A Hydroponic Vegetable Business Development Strategy: A Case Study of CV Casa Farm - sayekti, ayutyas; Putri, Deta Alifia Almi (SBM ITB, 2022)
Abstract. The Business Development Strategy for CV Casa Farm emerged from an analysis of the external and internal environments mapped using a SWOT matrix with a focus on weaknesses and opportunities. Several production problems, such as yellowing of vegetables, rotting roots, and the spread of disease that caused production failures and planting media waste, could be reduced to minimize costs and increase productivity to meet the demand for vegetables in the city of Bandung. Problems were also identified with management and governance, such as overlaps in the allocation of tasks causing unfavorable work performance and decreased productivity. Applying IoT technology could increase vegetable weight by 37.7% and reduce production failures from 12.85% to 7.14%. Based on non-financial factors, including the market, production, organization and management, human resources, and collaboration, the implementation of IoT technology was judged to be feasible. Based on a financial and partial analysis, the investment feasibility obtained NPV> 0 of Rp1,247,103,045.33, with a Net B/C value of 2.63, Gross B/C of 1.62, IRR acquisition of 31%, a payback period of four years and three months, and an increased profit of Rp27,849,345.00, the business development strategy was judged to be feasible using IoT Simon Kori technology because it met the investment criteria and brought additional benefits. In the sensitivity analysis, a 20% decrease in the product selling price was shown to have an impact on the feasibility of implementing IoT. An incremental net benefit analysis indicates that the net benefit from applying IoT technology would be Rp2,402.477,276.13.Keywords: CV Casa Farm, hydroponic vegetable, IoT technology, productivity improvement, SWOTAbstrak. Strategi Pengembangan Bisnis pada CV Casa Farm dibentuk berdasarkan analisis lingkungan eksternal dan internal yang dipetakan menggunakan matriks SWOT dengan berfokus pada kelemahan dan peluang. Terdapat beberapa permasalahan seperti sayur menguning, akar membusuk, penyebaran penyakit yang menyebabkan kegagalan produksi. Kegagalan produksi menyebabkan adanya limbah media tanam, Kegagalan dapat di minimalisir untuk memaksimalkan biaya yang dikeluarkan serta meningkatkan produktivitas perusahaan guna memenuhi permintaan sayur di Kota Bandung. Selain itu terdapat permasalahan pada tata Kelola manajemen yang kurang baik, seperti adanya tumpeng tindih dalam pembagian tugas yang menyebabkan kerja tidak kondusif dan produktifitas kerja menurun . Penerapan teknologi IoT dapat meningkatkan bobot sayur 37,7% dan meminimalisir kegagalan produksi dari 12,85% menjadi 7,14%. Berdasarkan aspek non finansial yang meliputi aspek pasar, produksi, organisasi dan manajemen, SDM, serta kolaborasi, penerapan teknologi IoT ini layak untuk dijalankan. Berdasarkan analisis finansial dan parsial, kelayakan investasi diperoleh NPV>0 sebesar Rp1.247.103.045,33, dengan nilai Net B/C sebesar 2,63, Gross B/C sebesar 1,62, perolehan IRR sebesar 31%), dengan Payback period sebesar 4 tahun 3 bulan, dan keuntungan tambahan sebesar Rp27.849.345,00, maka Strategi pengembangan bisnis dengan mengadopsi teknologi IoT Simon Kori pada CV Casa Farm layak untuk dijalankan karena memenuhi kriteria investasi dan terdapat keuntungan tambahan.Pada analisis sensitivitas, diketahui penurunan harga jual sebesar 20% berdampak pada kelayakan penerapan IoT Pada perhitungan analisis incremental net benefit, manfaat bersih dari penerapan teknologi IoT yaitu sebesar Rp2.402.477.276,13.Kata kunci: CV Casa Farm, peningkatan produktivitas, hidroponik, SWOT, teknologi IoT